Takwil dalam Tafsir Fath al-Qadir: Studi Analisis Pendekatan Linguistik - Unsiatun Naimah, Siti (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
The Qur’an was revealed as a guide for all of humanity, rich in linguistic style and profound in meaning. It contains two dimensions of interpretation: the ẓāhir (apparent) meaning and the bāṭin (inner, deeper) meaning. In this context, ta’wil is closely related to reason (‘aql) and understanding (dirāyah), functioning as a mental and conceptual process to uncover the deepest meanings of the text. Ta’wil is not limited to linguistic analysis but involves a holistic reading of phenomena, events, and realities that are intertwined with the text. This makes the intellect, knowledge, and imagination of the interpreter essential in the interpretive process. This study aims to analyze Imam ash-Syaukânî’s interpretive method in his tafsir Fath al-Qadîr through a linguistic approach. The research focuses on selected Qur’anic verses, particularly from theological, legal, and linguistic aspects. It employs library research as its methodology, with a descriptive-analytical approach. The findings show that Fath al-Qadîr extensively applies rhetorical principles (balâghah), such as isti‘ārah, majāz, kināyah, tamthīl, and ḥadhf. In this case, the linguistic approach is highly effective for uncovering implicit meanings, though it must adhere to linguistic rules to avoid misinterpretation.